Treadmill Training for Common Marmoset to Strengthen Corticospinal Connections After Thoracic Contusion Spinal Cord Injury - Kondo, Takahiro; Saito, Risa; Sato, Yuta; Sato, Kenta; Uchida, Akito; Yoshino-Saito, Kimika; Shinozaki, Munehisa; Tashiro, Syoichi; Nagoshi, Narihito; Nakamura, Masaya; Ushiba, Junichi; Okano, Hideyuki (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) leads to locomotor dysfunction. Locomotor rehabilitation promotes the recovery of stepping ability in lower mammals, but has limited efficacy in people with severe SCI. To explain this discrepancy between species, a non-human primate (NHP) rehabilitation model with severe SCI would be useful. In this study, we have developed a rehabilitation model with severe traumatic SCI leading paraplegia in NHP, the common marmoset (Callithrix jacchus). To assess the recovery of locomotor functions in marmosets precisely, the locomotor rating scale for marmosets was developed. All animals showed flaccid paralysis of the hindlimb after thoracic contusive SCI, and trained group showed significant locomotor recovery. Kinematic analysis showed hindlimb stepping patterns, which were significantly improved in the trained marmosets. Furthermore, intracortical microstimulation of the motor cortex evoked the hindlimb muscles in the trained group, suggesting a reconnection between the supraspinal input and the lumbosacral network. Since rehabilitation could be combined with regenerative interventions such as medicine or cell therapy, this primate model is useful as preclinical test of therapies that can be taken to human clinical trials.